Kemampuan Isolat Rizobakteri sebagai Agens Antagonis Fusarium verticillioides Penyebab Penyakit Busuk Tongkol pada Tanaman Jagung (Zea mays Linnaeus), secara Invitro: english - Martinius, Martinius; yunisman, yunisman; Harpani, Aisyah (Plant Protection Department, Faculty of Agriculture, Universitas Andalas, 2018)
Rhizobacteria is an alternative biocontrol of Fusarium verticillioides Sacc. Nirenberg caused ear rot on maize. The aim of this study was to screen rhizobacteria isolates that had ability as antagonist agent against F. verticillioides in vitro. Rhizobacteria was isolated from rhizosphere of healty maize from two villages of West Pasaman. Twenty six rhizobacteria isolates were obtained, then tested for hypersensitive reaction (HR), pectinase enzyme production, initial inhibitory activity, and hemolytic test. Two selected isolates: RBPas1 10-6 1 and RBPas2 10-5 2 could inhibit the growth of F. verticillioides. The inhibitory activity of both isolates were observed with dual culture method, using complete random design (CRD) with 2 treatments and 5 replications, furthermore physiological characterization was conducted. RBPas1 10-6 1 and RBPas2 10-5 2 isolates had the percentage inhibition of micelial growth: 46.16% and 31.30% respectively. Physiological characterization showed that RBPas1 10-6 1 was gram negative with baciliform cells, produced chitinase enzyme, siderophores and fluorescent. RBPas2 10-5 2 was gram positive with bacilliform cells, did not produce chitinase enzyme, siderophores and fluorescent.